THE EFFECT OF CAPITAL INTENSITY, INVENTORY INTENSITY, AND DEBT COVENANT ON TAX AVOIDANCE WITH SALES GROWTH AS A MODERATING VARIABLE - Daniel, Daniel; Handayani, Puspita (STIE Pelita Nusantara Semarang, 2025)
This study aims to analyze the influence of Capital Intensity, Inventory Intensity, and Debt Covenants on Tax Avoidance, with Sales Growth as a moderating variable. The research was conducted by analyzing the financial statements of Property & Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) from the official website of the Indonesia Stock Exchange (IDX) for the period 2019–2023. The sample used in this study consisted of 40 companies, with the sampling method employing purposive sampling. The data used in this study were secondary data in the form of financial statements and annual reports from each Property & Real Estate sector company included in the research sample. The study focuses on the variables Capital Intensity (X1), Inventory Intensity (X2), and Debt Covenant (X3) as independent variables, Tax Avoidance (Y) as the dependent variable, and Sales Growth (Z) as the moderating variable. The results show that the best-selected model for this study is the Random Effects Model (REM). The findings indicate that Capital Intensity, Inventory Intensity, and Debt Covenant do not individually influence Tax Avoidance. However, Sales Growth is only able to moderate the interaction between Capital Intensity and Tax Avoidance. Simultaneously, Capital Intensity, Inventory Intensity, and Debt Covenant collectively have an effect on Tax Avoidance.